Чернолаковая керамика из раскопок Никония 2008 - 2011 гг. - Глушек, И. (Материалы по археологии Северного Причерноморья, 2015)
The black-glazed ceramic from excavations of Nikonion in 2008–2011. The presents article deals with some black-glazed ceramic found during a series of archaeological campaigns realized at the east part of Nikonion in 2008–2011. The black-glazed ceramic testifies about bright trade between Nikonion and Attic in V–III centuries BC.